E-cigarette use and potential lung cancer risk: a systematic review - Villavicencio, Jordy M.; Coloma, Saúl A.; Véliz, Zulymar H.; Turibbi, Lailimar V.; Espinoza, Alisson A.; Rivadeneira, María A.; Galarza, Judith (Revista Gregoriana de Ciencias de la Salud, 2025)
The use of electronic cigarettes has significantly increased in recent years, particularly among young populations, raising concerns about their potential impact on respiratory health. This systematic review aimed to synthesize the available evidence regarding the association between electronic cigarette use and the risk of developing lung cancer. Systematic reviews, meta-analyses, and review articles published in English between 2015 and 2024 were included, while studies with limited or outdated information were excluded. The findings indicate that the aerosols produced by these devices contain various toxic and potentially carcinogenic substances. However, current evidence remains insufficient to establish a definitive causal relationship between vaping and the onset of lung cancer. There is a clear need for long-term longitudinal studies to comprehensively assess the chronic effects of electronic cigarette use on pulmonary health.